“Lá e de volta outra vez”: a incursão pela graduação de medicina por um químico - Arruda, Eduardo Guimarães Ratier de (Universidade Federal de São Carlos, 2024)
A reflective narrative on a unique academic journey marked by the integration of knowledge in chemistry during the medical program, facing challenges such as the final PhD final examination, the COVID-19 pandemic, and the battle against anxiety during those six years of undergraduation. Upon entering the medical program with a constructivist methodology, it was necessary to integrate prior knowledge and use adverse experiences as catalysts for personal and professional growth. The constructivist approach in medicine led to effective learning and guided towards a patient-centered practice, recognizing the importance of individualities and promoting empathy and respect in clinical relationships. Upon completing this education, more than obtaining the title of a physician, one attains ethical and compassionate medical practice. A journey that reflects the ability to transform challenges into driving forces for the construction of a unique medical learning experience.
“There and back again”: a chemist’s our ourselves for a medical degree
Keywords: Metodologia ativa; Narrativa reflexiva; Medicina; Active learning; Reflective narrative; Medicine; CIENCIAS DA SAUDE::MEDICINA